Synthesis and characterisation of novel diketopyrrolopyrrole derivatives - Humphreys, Joshua (2018)
The main goal of this thesis was to design new small molecule DPP derivatives, which could have a multitude of potential applications in areas such as organic electronics and sensors. Based on literature precedent, four factors were chosen to manipulate in the design of novel DPP systems: the electron richness of the aryl unit, π - π stacking, chirality and hydrogen bonding. The influence of these modifications to the DPP system on the optical, electronic and structural properties was then investigated to screen materials for potential applications in the aforementioned areas and to gain greater understanding for future molecular design in terms of structure–property relationships.